2022
DOI: 10.3233/thc-191847
|View full text |Cite
|
Sign up to set email alerts
|

Liver function, quantified by the LiMAx test, as a predictor for the clinical outcome of critically ill patients treated with linezolid

Abstract: BACKGROUND: Critically ill patients commonly suffer from infections that require antimicrobial therapy. In previous studies, liver dysfunction was shown to have an essential impact on the dose selection in these patients. This pilot study aims to assess the influence of liver dysfunction, measured by the novel LiMAx test, on clinical outcomes in critically ill patients treated with linezolid. METHODS: Twenty-nine critically ill patients were included and treated with linezolid. Indications for linezolid therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Wicha et al used the maximal liver function capacity (LiMAx test) tool for linezolid dose adjustment in patients with hepatic insufficiency. They suggested that TDM should be performed for LiMAx <100 μg/kg/h to reduce the risk of excessively high target plasma concentrations ( 62 , 63 ).…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
“…Wicha et al used the maximal liver function capacity (LiMAx test) tool for linezolid dose adjustment in patients with hepatic insufficiency. They suggested that TDM should be performed for LiMAx <100 μg/kg/h to reduce the risk of excessively high target plasma concentrations ( 62 , 63 ).…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
“…LiMAx ® achieved promising results for the assessment of hepatic function in liver resection, in liver transplantation [ 25 , 34 , 90 , 91 ], in monitoring antibiotics [ 27 , 29 , 92 ] and during sepsis [ 24 , 28 ]. The scope of applications may extend to monitor hepatic function during hemoadsorption with CytoSorb ® .…”
Section: Discussionmentioning
confidence: 99%
“…The LiMAx ® can serve as a guide and help to correctly assess the severity of SALD at an early stage. This diagnostic tool could make an important contribution to minimizing additional liver cell damage, e.g., by adjusting and monitoring liver toxic drugs such as antibiotics and antimycotics [ 24 , 27 , 28 , 29 , 31 , 92 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial inverse association between the LiMAx score and high linezolid trough concentration has also been reported. 24,25 They reported that for LiMAx ,100 mg/kg/h, 64% of the linezolid trough concentrations were above the recommended trough concentration of 8 mg/L. Cured patients presented lower median linezolid Cmin, yet a remarkably higher…”
Section: Impaired Hepatic Functionmentioning
confidence: 99%
“…A substantial inverse association between the LiMAx score and high linezolid trough concentration has also been reported. 24,25…”
Section: A Brief Introduction To Linezolid An Increasingly Important ...mentioning
confidence: 99%